This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Anish Kelkar You can take limits separately on terms in multiplication only if the number of terms is finite .. Here the number of terms is dependent on n .
n → ∞ l im ( ∏ r = 1 n 1 + n 2 r 2 ) 1 / n = n → ∞ l im ( 1 + n 2 1 ) 1 / n ⋅ n → ∞ l im ( 1 + n 2 2 ) 1 / n n → ∞ l im ( 1 + n 2 3 ) 1 / n ⋅ n → ∞ l im ( 1 + n 2 4 ) 1 / n . . . . . . . . n → ∞ l im ( 1 + n 2 n 2 ) 1 / n ⋅ = n → ∞ l im e 1 / n 3 ⋅ e 2 2 / n 3 ⋅ e 3 2 / n 3 ⋅ e 4 2 / n 3 ⋅ . . . . . . . . . . . . . e n 2 / n 3 ⋅ = n → ∞ l im e 6 n ( n + 1 ) ( 2 n + 1 ) n 3 = e 3 1
Log in to reply
Sir I have some problem in ur second line.....ok n is a variable mind it...if it is a constant it was perfectly ok...see this stuff u can write x^2=x+x+....+x....differentiate both sides u get 2x=x...so where is the fallacy?It is that x is a variable no. so u can not apply that theorem that d(cx)/dx=c where c is a constant.Ok sir this is what I think I may be completely wrong if u have anything to say pls kindly do.Thanks.
@Anish Kelkar You cannot take the limit individually on the brackets like that
Same as I did it.
Did you forget to add this to the problem statement ? -- " This too is a standard problem in most calculus textbooks for JEE(Advanced) " Just kidding ! : P .
How did you convert that sum into the integral?
Log in to reply
Using the concept of Riemann sum n → ∞ lim n 1 r = f ( n ) ∑ g ( n ) h ( n r ) = n → ∞ lim ∫ f ( n ) / n g ( n ) / n h ( x ) d x if n → ∞ lim n f ( n ) is finite
well if we simply solve it using limits . answer comes out to be e^(1/3)
Well I donot think any mistake in it as it is a well defined property of limit of product of functions . ( NCERT Pg 292 Class XI)
I am unable to understand where my mistake is ??
yeah ! did same :) but it's bit over-rated .
Easy problem dude
Problem Loading...
Note Loading...
Set Loading...
Let the limit we need to find be L .
L = n → ∞ lim k = 1 ∏ n n a ( k , n ) = n → ∞ lim k = 1 ∏ n n 1 + n 2 k 2 = n → ∞ lim n ( 1 + n 2 1 2 ) ( 1 + n 2 2 2 ) . . . . ( 1 + n 2 n 2 )
Taking natural logarithm on both the sides to convert the limit in question into a sum,
lo g L ∴ L = n → ∞ lim n 1 lo g ( ( 1 + n 2 1 2 ) ( 1 + n 2 2 2 ) . . . . ( 1 + n 2 n 2 ) ) = n → ∞ lim n 1 r = 1 ∑ n lo g ( 1 + n 2 r 2 ) = n → ∞ lim ∫ 1 / n n / n lo g ( 1 + x 2 ) d x = ∫ 0 1 lo g ( 1 + x 2 ) d x = e ∫ 0 1 lo g ( 1 + x 2 ) d x
Now to find the integral, we use IBP →
∫ 0 1 lo g ( 1 + x 2 ) d x = x lo g ( 1 + x 2 ) ∣ ∣ 0 1 − ∫ 0 1 x 1 + x 2 2 x d x = lo g 2 − ∫ 0 1 2 − 1 + x 2 2 d x = lo g 2 − 2 x − 2 tan − 1 x ∣ ∣ 0 1 = lo g 2 + 2 π − 2
So, L = 2 e π / 2 − 2 ≈ 1 . 3 0 2